Pengaruh Brand Image, Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Cat Propan Cabang Palembang - Sulaiman Sulaiman; Sulaiman Helmi (Benefit: Journal of Bussiness, Economics, and Finance, 2025)
This study focuses on the analysis of the influence of brand image, product quality, and price on the purchase decision of Propan paint in the Palembang Branch. The basis of this study is the high competition in the paint industry, where the Company must be able to create a solid brand image, product quality, and provide competitive prices to attract consumers. The method applied in this study is a quantitative method using a survey. Data collection was carried out by distributing questionnaires to 100 respondents who were consumers of Propan paint in the Palembang area. To analyze the data, multiple linear regression techniques were used to understand the influence of each independent variable on the dependent variable. The results of the study showed that brand image, product quality, and price had a positive and significant effect on the purchase decision of Propan paint, both partially and simultaneously. Among the three factors, product quality has the greatest impact on purchasing decisions. This finding suggests that companies need to continue to improve product quality and strengthen brand image and pricing strategies in order to maintain and increase consumer purchasing interest.